2021
DOI: 10.1021/jasms.1c00225
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Effects of Methylation on the CID of Protonated Lysine: A Combined Experimental and Computational Approach

Abstract: We report the results of experiments, simulations, and DFT calculations that focus on describing the reaction dynamics observed within the collision-induced dissociation of Llysine-H + and its side-chain methylated analogues, N ε -methyl-Llysine-H + (Me 1 -lysine-H + ), N ε ,N ε -dimethyl-L-lysine-H + (Me 2 -lysine-H + ), and N ε ,N ε ,N ε -trimethyl-L-lysine-H + (Me 3 -lysine-H + ). The major pathways observed in the experimental measurements were m/z 130 and 84, with the former dominant at low collision ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…The initial structure of p-Ser was determined using Avogadro [25] with the phosphorylation occurring on the side-chain oxygen and the excess proton placed on the N-terminus. Direct dynamics simulations involving protonated peptides are commonly performed with PM6 [17,26] and the RM1 [16,21,22,[26][27][28][29] semi-empirical methods. In our study of s-Ser, we found that PM6 outperformed RM1 [17], and expect similar results to be seen here.…”
Section: Direct Dynamics Simulation Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The initial structure of p-Ser was determined using Avogadro [25] with the phosphorylation occurring on the side-chain oxygen and the excess proton placed on the N-terminus. Direct dynamics simulations involving protonated peptides are commonly performed with PM6 [17,26] and the RM1 [16,21,22,[26][27][28][29] semi-empirical methods. In our study of s-Ser, we found that PM6 outperformed RM1 [17], and expect similar results to be seen here.…”
Section: Direct Dynamics Simulation Methodsmentioning
confidence: 99%
“…Proton motion can be correlated to fragmentation times, allowing for an analysis of the influence of these migrations on dissociation events [35]. It was recently illustrated that this type of information could be combined with a graph theory analysis [16,36,37] to define a modified ad-jacency matrix weighted by the atomic number whose lowest eigenvalue is used to identify unique structures. Graph theory and direct dynamics provide powerful tools for analyzing reaction mechanisms.…”
Section: Theoretical Mass Spectra and Reaction Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations
“…Direct dynamics simulations [15][16][17][18][19][20][21] and ab initio calculations have a history of providing significant and impactful insight into the dynamics taking place in tandem mass spectrometry. However, only a few systems that contain PTMs have been studied using these techniques.…”
Section: Introductionmentioning
confidence: 99%